Marketing of Illegal Cigarettes from a Legal Perspective in Indonesia - Prayitno, Rangga; Agussalim M; Irwan Febrianto (The Future of Education Journal, 2026)
The marketing of illegal cigarettes is a growing phenomenon in Indonesia and poses serious impacts on state revenue, fair business competition, and public health protection. Illegal cigarettes are generally marketed without excise tax stamps or by using counterfeit excise stamps, both through conventional distribution channels and digital media. This article aims to analyze the legal framework governing the marketing of illegal cigarettes, the forms of marketing practices that occur in practice, and the effectiveness of law enforcement carried out by the competent authorities. The research method employed is normative legal research using statutory and conceptual approaches. The findings indicate that although the legal regulation of excise has been comprehensively and strictly stipulated, the marketing of illegal cigarettes remains widespread due to weak supervision, economic factors, and low public legal awareness. Therefore, strengthening law enforcement and enhancing inter-agency synergy are necessary to suppress the circulation of illegal cigarettes in Indonesia.